Efektivitas Model Cooperative Learning terhadap Keaktifan Belajar Siswa dalam Pembelajaran Matematika Tingkat SMP - Maulida, Khilda Sally; Heni Pujiastuti; Abdul Fatah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The aim of this research was to explore how much cooperative learning frameworks can enhance student engagement during mathematics lessons in high school. The issue tackled in this research is the inadequate student involvement stemming from teaching approaches that focus mainly on the instructor. This study relies on a comprehensive review of 19 pertinent articles released from 2018 to 2026, sourced from numerous academic databases, including Google Scholar, and others. Data analysis was conducted through a qualitative-descriptive method. Findings indicate that several cooperative learning models, such as Think Pair Share, Student Teams Achievement Division, Jigsaw, Team Games Tournament, Buzz Group, Team Assisted Individualization, Make a Match, and Group Investigation, have been effective in enhancing student learning engagements. This enhancement is evident in the increased student participation in activities such as asking and answering questions, engaging in discussions, presenting, and working collaboratively in groups. In summary, the use of cooperative learning models is crucial in boosting student learning activities and fostering a more interactive and learner-focused educational atmosphere.